A Proposed Framework for Assessing the Readiness of AI in Small and Medium Enterprises (SMEs) in Malaysia - Yen, Wendy Teoh Ming; Hong, Tan Lay; Yen, Yuen Yee (Journal of Ecohumanism, 2024)
Small and Medium Enterprises (SMEs) have become increasingly important to Malaysia’s economy in recent years. They contribute significantly to GDP growth, job creation, and innovation. However, SMEs often face various challenges such as limited resources, market competition, and technological barriers. In this digital age, integrating Artificial Intelligence (AI) has tremendous potential to overcome these challenges and drive SMEs towards sustainable growth and competitiveness. Despite this, it remains unclear whether Malaysian SMEs are ready to adopt and use AI technologies. This research aims to bridge this gap by investigating the readiness of Malaysian SMEs to embrace AI, the factors that influence their readiness, and the potential impact of AI integration on their business performance and competitiveness. This initiative aligns with the National Science, Technology, and Innovation Policy (NSTIP) 2021-2030, i.e., promoting the development and readiness of local technology. This study proposes a conceptual framework to provide a detailed understanding of the readiness of Malaysian SMEs to adopt AI, analyze the factors that influence AI readiness, and evaluate the potential impact of AI integration on their business performance and competitiveness. The findings will inform future research initiatives aimed at enhancing SME competitiveness and fostering innovation in Malaysia’s business ecosystem.